Joint- and subject-specific strategies in male basketball players across a range of countermovement jump heights - Kipp, K.; Kiely, K.; Giordanelli, M.; Malloy, P.; Geiser, C. (Journal of Sports Sciences, 2020)
The purpose of this study was to investigate subject- and joint-specific strategies used by male basketball players as they increase their countermovement jump (CMJ) height from sub-maximal to maximal efforts. Lower extremity joint kinematics and kinetics were recorded as 11 male, NCAA Division I basketball players performed 8-10 CMJ across effort levels of approximately 25%, 50%, 75% and 100%. Simple correlation models were used to investigate the associations between effort levels (i.e., CMJ height) and joint mechanics (i.e., negative (eccentric) and positive (concentric) mechanical work performed at the hip, knee, and ankle joints) for each individual player and the entire group. Group-analyses showed that increases in all joint mechanical variables were associated with increases in CMJ height. In contrast, single-subject analyses revealed that players used individualised strategies, and selectively scaled the magnitude of mechanical work at none (n = 2), one (n = 2), two (n = 5), or all three (n = 2) joints as they increased CMJ efforts. In addition, individual players also appeared to selectively scale different combinations of eccentric or concentric joint work as they increased CMJ height. These results highlight that male basketball players use joint-specific strategies to increase CMJ height when progressively increasing CMJ effort.